Effects of Enteral Nutrition on Patients With Oesophageal Carcinoma Treated With Concurrent Chemoradiotherapy: A Prospective, Multicentre, Randomised, Controlled Study - Lyu, Jiahua; Shi, Anhui; Li, Tao; Li, Jie; Zhao, Ren; Zhu, Shuchai; Wang, Jianhua; Xing, Ligang; Yang, Daoke; Xie, Conghua; Shen, Liangfang; Zhang, Hailin; et al. (Frontiers in Oncology, 2022)
Background The oesophageal carcinoma patients show high incidence of malnutrition, which negatively affects their therapy outcome. Moreover, benefits of enteral nutrition remain to be studied in details in these patients. Therefore, we set to assess the effects of enteral nutrition on the nutritional status, treatment toxicities and survival in the oesophageal carcinoma patients treated with concurrent chemoradiotherapy (CCRT). Materials and Methods Eligible patients were randomly assigned to either the experimental or control group. The patients in the experimental group were treated with a whole-course enteral nutrition management, while the control group were provided a unsystematic nutrition without setting intake goals for energy and protein. The primary endpoint was a change in body weight, while the secondary endpoints included nutrition-related haematological indicators, toxicities, completion rate of treatment and survival. Results A total of 222 patients were randomised to either the experimental (n=148) or control (n=74) group. Patients in the experimental group showed significantly less decrease in body weight, serum albumin and haemoglobin levels, a lower incidence rates of grade ≥3 myelosuppression and infection, and a higher completion rate of CCRT than those in the control group. While analyses of the 2 and 3 year overall survival (OS) and progression-free survival (PFS) did not reveal differences between these groups, we observed a significantly higher OS at 1 year (83.6% vs. 70.0%). In the subgroup analysis, patients with patient-generated subjective global assessment (PG-SGA)=C were likely to have better OS and PFS with enteral nutrition. Conclusions In EC patients treated with CCRT, enteral nutrition conferred positive effects on the nutritional status, treatment toxicities and prognosis, which mandate its inclusion in clinical practice. Clinical Trial Registration This prospective trial has been registered with www.clinicaltrials.gov as NCT02399306.